Quality of service based hierarchical resource allocation algorithm - Cheng DING; Jinrong CHEN; Xiaodong CAO; Yi WANG (Dianxin kexue)
Wireless sensor network (WSN) is widely used in the internet of things (IoT) scene because of its small size, low cost and strong sensing ability.How to improve the quality of service (QoS) under the premise of load balancing in WSN has become the focus of many scholars.Based on the study of heuristic resource allocation method and hierarchical structure resource allocation method in WSN, a quality of service based hierarchical resource allocation algorithm (QoSHRA) was proposed.Firstly, the resource allocation method based on low energy adaptive clustering hierarchy (LEACH) made the whole network form a hierarchical structure.Then, QoSHRA was used for resource allocation.The simulation results show that QoSHRA can further save the energy consumption of network transmission, ensure the effectiveness of service allocation, and improve the satisfaction rate of network resource QoS requirements on the premise of ensuring network load balancing.